Effects of norgestrel on the reproductive endocrine system, hepatic damage and antioxidant responses of marine medaka (Oryzias melastigma) at different salinities - Jian Song; Chao Zheng; Yan-Qiu Liang; Zhongdian Dong; Chang-Gui Pan; Wen-Jun Shi; Qidan Zheng; Shuhui Zhou; Mingwei He; Xipeng Mo; Zhong Lin (Aquatic Toxicology, 2026)

Precise perception of surface tackiness enabled by a soft single-sensing-element tactile sensor - Ying Yang; Mingwei Gu; Jia-Sen Xie; Xingyu Ma; Yan-Na Lu; Lin Zheng; Jinhui Gu; Junshuai Chen; Yunjie Lu; Denys Makarov; Jin Ge (Science Bulletin, 2026)

Optimization of multi-enzyme coupled debittering process: Effect on bitterness and bioactive components of Shatianyu (Citrus grandis L. Osbeck) whole fruit powder - Lin Zhang; Ruifen Zhang; Mingwei Zhang; Zhenlin Xu; Fei Huang; Xuchao Jia; Lihong Dong; Zhiming Wang; Mei Deng (Food Chemistry, 2026)

Wave flow field design optimization for enhanced performance of high-temperature PEM fuel cells - Mingwei Li; Lirong Fu; Huadong Lin; Jinyi Liu; Xiaosong Zhang (Fuel, 2026)

FINDER: Flow-aware intelligent navigation through distilled experience and reinforcement learning for UUVs in complex flow fields - Shuguang Chu; Haihan Feng; Yuheng Ou; Mingwei Lin; Dejun Li (Ocean Engineering, 2026)

RAD51 m6A and PARylation modification orchestrate benzene-induced haematological toxicity - Lin Chen; Fengzhen Cui; Han Li; YuTao Zeng; Zhongming Wu; Weitian Chen; Qiaosheng Wen; Chunnian You; Yunqiang Xu; Lei Sun; Mingwei Sun; Qian Sun; et al. (Journal of Hazardous Materials, 2026)

Separation of gallium from acid leachates of zinc smelting slag by tartaric acid coordinated complexation and anion-exchange - Mingwei Qi; Minyu Zhu; Hao Chen; Yun Liu; Zhiqiang Lin; Zezuo Jiang; Jing Wu; Chunlin He (Hydrometallurgy, 2026)

Using geo-data and social media images to explore the supply and demand of cultural ecosystem services for terraces in China - Song Chen; Xiyue Wang; Tianming Liu; Mingwei Xie; Qing Lin (Ecosystem Services, 2025)

Pig bedding biochar enhances the Cd extraction capacity of Perilla frutescens by mitigating the toxicity of Cd-contaminated soil - Tianlian He; Xingyu Hao; Rui Jing; Zhenguo Li; Ying Chen; Mingwei Yang; Chengzhen Gu; Yulin Wang; Ruiyu Lin; Xinyu Zheng (Journal of Environmental Sciences, 2025)

Corrigendum to “Engineered zwitterionic hydrogel with extreme environment resilience: High ionic conductivity, subzero tolerance, and potential for multimodal sensing and optical applications across devices” [Chem. Eng. J. 510 (2025) 161390/CEJ 161390] - Yan-Na Lu; Kai Mo; Mingwei Gu; Jia-Sen Xie; Ying Yang; Lin Zheng; Xiang-Ru Liu; Yunjie Lu; Jun-Shuai Chen; Jin Ge (Chemical Engineering Journal, 2025)

MiR-223-3p inhibits hippocampal neurons injury and exerts anti- anxiety/depression-like behaviors by directly targeting NLRP3 - Wenyuan Wang; Tingting Yang; Na Liu; Lin Yang; Cong Liu; Xiaoxiao Qi; Ning Wang; Mingwei Wang; Yanyong Wang (Psychopharmacology, 2025)

Analysis of CO2 emission and energy consumption in CCUS for steel-chemical joint production - Huapeng Yang; Chao Feng; Tao Lin; Rong Zhu; Kai Dong; Guangsheng Wei; Mingwei Tu; Fuhai Liu; Ziheng Zhao; Xin Ren; Chunyang Wang (Journal of Environmental Management, 2025)

Enhanced oil recovery through CO2 injection: The role of pentane in improving miscibility of CO2 and oil - Mingwei Zhao; Yuxin Xie; Xiangjuan Meng; Lin Li; Caili Dai; Zhihao Zhang; Zhenfeng Ma; Yingnan Wang; Zhongzheng Xu; Xuguang Song (Fuel, 2025)

RAPID LEAF FALLING 1 facilitates chemical defoliation and mechanical harvesting in cotton - Bing Zhang; Dandan Yue; Bei Han; Danfan Bao; Xiao Zhang; Xuyang Hao; Xin Lin; Keith Lindsey; Longfu Zhu; Shuangxia Jin; Maojun Wang; Haijiang Xu; et al. (Molecular Plant, 2025)

Chlorella-regeneration of exhausted D301-Zr nanocomposite adsorbent of phosphate sequestration from water: A multi benefits approach with adsorbent regeneration, phosphorus reuse, and carbon fixation - Mingwei Fu; Mingyang Lin; Sufeng Wang; Jingshan Li (Journal of Water Process Engineering, 2025)

Ultra-high temperature and salinity resistant microspheres featuring “Rigid hydrophobic core- soft hydrophilic Shell” structure for deep reservoir profile control - Wei Xiang; Lin Li; Yunbo Dong; Zizhao Wang; Zifan Song; Mingwei Zhao; Caili Dai (Chemical Engineering Journal, 2025)

Engineered zwitterionic hydrogel with extreme environment resilience: High ionic conductivity, subzero tolerance, and potential for multimodal sensing and optical applications across devices - Yan-Na Lu; Kai Mo; Mingwei Gu; Jia-Sen Xie; Ying Yang; Lin Zheng; Xiang-Ru Liu; Yunjie Lu; Jun-Shuai Chen; Jin Ge (Chemical Engineering Journal, 2025)

Adaptive reward shaping based reinforcement learning for docking control of autonomous underwater vehicles - Shuguang Chu; Mingwei Lin; Dejun Li; Ri Lin; Sa Xiao (Ocean Engineering, 2025)

AOPPs induces EMT and fibrosis by activating oxidative stress through ERK/p38 MAPK signaling pathway in endometriosis - Xiaoqing Luo; Sixi Wen; Junling Zeng; Jing Liu; Wenting Ye; Jiangpeng Wu; Songyu Huang; Wuwei Xie; Haiping Wen; Yan Sun; Jing Cai; Daidi Mo; et al. (Reproductive Biology, 2024)

Frequency optimization of the AUV wireless charging system for minimum energy dissipation - Ri Lin; Mingwei Lin; Canjun Yang; Dejun Li; Zhuoyu Zhang (Ocean Engineering, 2024)

Static Model of the Underwater Soft Bending Actuator Based on the Elliptic Integral Function - Ri Lin; Anzhe Yi; Mingwei Lin; Canjun Yang; Zhuoyu Zhang (Journal of Marine Science and Engineering, 2024)
Underwater soft manipulators are increasingly used for grasping underwater organisms and cultural relics due to their compliance and ability to protect delicate objects. Unlike rigid manipulators, these soft manipulators feature underwater soft bending actuators that deform under external forces, making their shape and output force challenging to predict. Consequently, classical beam theory is no longer applicable. To address these issues, this article models the underwater soft bending actuator as a cantilever beam and establishes its shape and output force using elliptic integral functions. Additionally, this article proposes a method for determining the unknown parameters of the driver shape and output force model using optimization techniques and introduces a solution process based on the particle swarm optimization framework. Given the role of tensile and bending stiffness in the actuator’s performance, this paper employs a parameter identification method based on length and bending angle information. Tests demonstrate that the proposed method effectively estimates the deformation and output force of the underwater soft bending actuators, confirming its accuracy.

Underwater fluid-driven soft dock for dynamic recovery of AUVs with improved pose tolerance - Mingwei Lin; Anzhe Yi; Ri Lin; Xin Wu; Bohao He; Bolun Zhang; Canjun Yang (Ocean Engineering, 2024)

Gaze-Assisted Prescribed Performance Controller for AUV Trajectory Tracking in Time-Varying Currents - Zhuoyu Zhang; Mingwei Lin; Dejun Li; Ri Lin (Journal of Marine Science and Engineering, 2024)
Trajectory tracking for underactuated autonomous underwater vehicles (AUVs) is challenging due to coupling dynamics, modeling inaccuracies, and unknown disturbances. To tackle this, we propose a decoupling gaze-assisted prescribed performance controller (GAPPC). We first use an error transformation approach to achieve the prescribed performance, incorporating the line-of-sight (LOS) algorithm and an event-triggering mechanism to handle the kinematic characteristics of underactuated AUVs. Next, we develop a control strategy for the transformed error that does not require knowledge of the model parameters, including fast dynamic compensation to reduce steady-state errors. Finally, we analyze the controller’s stability and present simulation results. Simulations, which account for modeling inaccuracies and unknown ocean currents, show that the GAPPC improves stability errors by 67.3% compared to the adaptive robust controller.

Bamboo vinegar regulates the phytoremediation efficiency of Perilla frutescens (L.) Britt. by reducing membrane lipid damage and increasing cadmium retention - Zhenguo Li; Xingyu Hao; Tianlian He; Ying Chen; Mingwei Yang; Cheng Rong; Chengzhen Gu; Qingtie Xiao; Ruiyu Lin; Xinyu Zheng (Journal of Hazardous Materials, 2024)

Nanofluids with superhydrophobic nanoparticles for improved depressurization mechanism in low permeability reservoirs - Mingwei Zhao; Yuxin Xie; Lin Li; Caili Dai; Zhongzheng Xu; Yunbo Dong; Hongbo Zeng (Chemical Engineering Journal, 2024)

Image stitching and target perception for Autonomous Underwater Vehicle-collected side-scan sonar images - Zhuoyu Zhang; Rundong Wu; Dejun Li; Mingwei Lin; Sa Xiao; Ri Lin (Frontiers in Marine Science, 2024)
Introduction Autonomous Underwater Vehicles (AUVs) are capable of independently performing underwater navigation tasks, with side-scan sonar being a primary tool for underwater detection. The integration of these two technologies enables autonomous monitoring of the marine environment. Methods To address the limitations of existing seabed detection methods, such as insufficient robustness and high complexity, this study proposes a comprehensive seabed detection method based on a sliding window technique. Additionally, this study introduces a sonar image stitching method that accounts for variations in image intensity and addresses challenges arising from multi-frame overlaps and gaps. Furthermore, an autonomous target perception framework based on shadow region segmentation is proposed, which not only identifies targets in side-scan sonar images but also provides target height measurements. Results Comprehensive seabed detection method improves accuracy by 31.2% compared to the peak detection method. In experiments, the height measurement error for this method was found to be 9%. Discussion To validate the effectiveness of the proposed seabed detection method, sonar image stitching method, and target perception framework, comprehensive experiments were conducted in the Qingjiang area of Hubei Province. The results obtained from the lake environment demonstrated the effectiveness of the proposed methods.

Autonomous Underwater Vehicle Cruise Positioning and Docking Guidance Scheme - Zhuoyu Zhang; Wangjie Ding; Rundong Wu; Mingwei Lin; Dejun Li; Ri Lin (Journal of Marine Science and Engineering, 2024)
The Autonomous Underwater Vehicle (AUV) is capable of autonomously conducting underwater cruising tasks. When combined with docking operations, the AUV can replenish its electric power after long-distance travel, enabling it to achieve long-range autonomous monitoring. This paper proposes a positioning method for the cruising and docking stages of AUVs. Firstly, a vision guidance algorithm based on monocular vision and threshold segmentation is studied to address the issue of regional noise that commonly occurs during underwater docking. A solution for regional noise based on threshold segmentation and proportional circle selection is proposed. Secondly, in order to enhance the positioning accuracy during the cruising stage, a fusion positioning algorithm based on particle filtering is presented, incorporating the Doppler Velocity Log (DVL) and GPS carried by the AUV. In simulation, this algorithm improves positioning accuracy by over 56.0% compared to using individual sensors alone. Finally, experiments for cruising and docking were conducted in Qingjiang, Hubei, China. The effectiveness of both methods is demonstrated, with successful docking achieved in four out of five attempts.

Cancer screening in hospitalized ischemic stroke patients: a multicenter study focused on multiparametric analysis to improve management of occult cancers - Jie Fang; Jielong Wu; Ganji Hong; Liangcheng Zheng; Lu Yu; Xiuping Liu; Pan Lin; Zhenzhen Yu; Dan Chen; Qing Lin; Chuya Jing; Qiuhong Zhang; et al. (EPMA Journal, 2024)

Study on formation process and reservoir damage mechanism of blockages caused by polyacrylamide fracturing fluid in production wells - Zhongzheng Xu; Mingwei Zhao; Jiawei Liu; Yiming Zhang; Mingwei Gao; Xuguang Song; Ning Sun; Lin Li; Yining Wu; Caili Dai (Fuel, 2024)

Insight into functional groups of salt compounds on the performance of viscoelastic surfactant-based fluids - Xiangyu Wang; Zhengjian Hou; Mingwei Zhao; Xuhao Wang; Peng Liu; Xufeng Lin; Zizhao Wang; Zhenfeng Ma; Caili Dai (Fuel, 2024)

A polylactide based multifunctional hydrophobic film for tracking evaluation and maintaining beef freshness by an electrospinning technique - Xinxin Liu; Xiushuang Song; Dejiao Gou; Hongli Li; Lin Jiang; Minglong Yuan; Mingwei Yuan (Food Chemistry, 2023)

Concatenated dynamic DNA network modulated SERS aptasensor based on gold-magnetic nanochains and Au@Ag nanoparticles for enzyme-free amplification analysis of tetracycline - Yan Lv; Shuo Qi; Imran Mahmood Khan; Xiaoze Dong; Mingwei Qin; Lin Yue; Yin Zhang; Zhouping Wang (Analytica Chimica Acta, 2023)

Development of a Radially Coupled Wireless Charging System for Torpedo-Shaped Autonomous Underwater Vehicles - Mingwei Lin; Ri Lin; Dejun Li; Runtian Duan (Journal of Marine Science and Engineering, 2023)
Spiral coaxial coils are widely used in wireless charging systems for autonomous underwater vehicles (AUVs). However, these coils can generate axial electromagnetic interference that may adversely affect the electronic components contained within the AUV. In order to overcome this issue, this paper introduced a pair of radially coupled coils which implement distributed ferrite cores. The mathematical model of the curly coils was derived, and its geometry parameters were optimized through the use of genetic algorithms. ANSYS Maxwell was used to analyze and optimize the layout of the ferrite cores. A prototype of the AUV wireless charging system was presented, demonstrating a maximum efficiency of 94% at 2.2 kW in salt water. The rotation adaptivity of the system was also tested, revealing stable output performance within the possible roll-angle variations of the AUV.

Investigation of additive-assisted microbial-induced calcium carbonate precipitation in 3D printed cross fractures - Liang Guo; Min Zhang; Mingwei Liao; Baoquan Wang; Xiaoyu He; Yiqi Peng; Xingzhu Lin; Ni He; Zhuhong Xiong; Han Chen; Yehui Shi; Tong Li (Geomechanics for Energy and the Environment, 2023)

Carbon neutrality: a comprehensive bibliometric analysis - Lili Zhang; Jie Ling; Mingwei Lin (Environmental Science and Pollution Research, 2023)

Bio-inspired superhydrophobic interface of nano-gaseous film for reducing injection pressure in oil reservoirs - Zhongzheng Xu; Mingwei Zhao; Yiming Zhang; Pan Wang; Yining Wu; Lin Li; Xin Cui; Ning Sun; Caili Dai (Chemical Engineering Journal, 2023)

Compound Probiotic Ameliorates Acute Alcoholic Liver Disease in Mice by Modulating Gut Microbiota and Maintaining Intestinal Barrier - Haixia Liu; Xing Kang; Xiaodan Yang; Hao Yang; Xiaoyu Kuang; Peng Ren; Huan Yan; Xiaorong Shen; Yongbo Kang; Lin Li; Xiaohui Wang; Linzhi Guo; et al. (Probiotics and Antimicrobial Proteins, 2023)

Experimental investigation on spontaneous combustion oxidation characteristics and stages of coal with different metamorphic degrees - Baisheng Nie; Hongwei Yan; Peijun Liu; Zongyu Chen; Chao Peng; Xiaotong Wang; Feifei Yin; Jie Gong; Yueying Wei; Shuangshuang Lin; Qiang Gao; Mingwei Cao (Environmental Science and Pollution Research, 2023)

Underwater Electromagnetic Guidance Based on the Magnetic Dipole Model Applied in AUV Terminal Docking - Ri Lin; Yucheng Zhao; Dejun Li; Mingwei Lin; Canjun Yang (Journal of Marine Science and Engineering, 2022)
To address the poor effect of optical/visual guidance used in AUV terminal docking with strong background light and turbid water quality, an underwater electromagnetic guidance method based on the magnetic dipole model is proposed in this paper. According to the magnetic dipole model, the electromagnetic field of 1 kHz frequency generated by the coil in the range of terminal docking is the near field, where the position can be figured out through the amplitude and phase information of three orthogonal magnetic field intensity vectors. A triaxial-coil magnetometer with three orthogonal coils and a method for extracting the amplitude and phase information of the induced voltage are presented in this paper. According to Faraday’s law, the amplitude and phase information of the induced voltage of a triaxial-coil magnetometer replace the information of magnetic field intensity in relation to positioning. The underwater positioning results show that the average positioning error within 6 m can reach the centimeter level. Five underwater terminal docking tasks were carried out, and four of them were successfully completed, which verified the feasibility of the proposed method.

Evaluation on explosion characteristics and parameters of pulverized coal for low-quality coal: experimental study and analysis - Hongwei Yan; Baisheng Nie; Chao Peng; Peijun Liu; Xiaotong Wang; Feifei Yin; Jie Gong; Yueying Wei; Shuangshuang Lin; Qiang Gao; Mingwei Cao (Environmental Science and Pollution Research, 2022)

Proteomics provides individualized options of precision medicine for patients with gastric cancer - Wenwen Huang; Dongdong Zhan; Yazhuo Li; Nairen Zheng; Xin Wei; Bin Bai; Kecheng Zhang; Mingwei Liu; Xuefei Zhao; Xiaotian Ni; Xia Xia; Jinwen Shi; et al. (Science China Life Sciences, 2021)

Buoyancy Regulation Strategy for Underwater Profiler Based on Adaptive Genetic Algorithm - Hui Zhi; Puzhe Zhou; Yanhu Chen; Xiaoyan Zhao; Yuandong Hong; Mingwei Lin; Canjun Yang (Journal of Marine Science and Engineering, 2021)
Considering the energy limitations of underwater vehicles, a strategy for energy saving is proposed. In the proposed buoyancy regulation strategy, oil of the buoyancy regulation system is pumped out several times at different depths instead of all at once. A balance between energy and time is achieved by assigning suitable weights, and the optimised depth which can be obtained from the pressure sensor is used as the judgement threshold based on the adaptive genetic algorithm. Through the numerical simulation using sea trial data, the influence of weight selection on energy and time is explored, and the frequency of oil draining for the vehicle to ascend is optimised. Simulation results show that the proposed buoyancy regulation strategy can save energy effectively when the frequency of oil draining is 4 times within depths of 0–500 m. Finally, trials were performed in Qiandao Lake and verify the contradictory relationship between energy and time.

Numerical Simulation of Wave Interaction with Payloads of Different Postures Using OpenFOAM - Mingwei Yan; Xin Ma; Wei Bai; Zaibin Lin; Yibin Li (Journal of Marine Science and Engineering, 2020)
A three-dimensional numerical wave tank (NWT) is established with Open Source Field Operation and Manipulation (OpenFOAM) software and waves2foam to investigate wave interaction with payloads with different postures in the process of offshore lifting or lowering. Numerical results of regular wave interaction with a vertically suspending cylinder are presented first for validation by comparison with the published data. A series of simulation experiments are carried out, and the forces and the moments exerted by the regular waves on a fixed suspending cylinder payload and a fixed suspending cuboid payload with different postures are presented. It can be concluded from the results that the rotating rectangular payload (cuboid and cylinder) suffers a drastically changed moment when it is initially vertically placed, and the projection area of payload vertical to the force affects the corresponding force. The simulation results also show how the forces and the moments change with different posture angles. With some certain posture, the suspending payload suffers minimum forces and moments. Parametric study for the cuboid payload is done in the case of normal incidence. The influence of the payload’s size and wave parameters on forces and moments are analyzed. All of the numerical simulation results and conclusions provide the fundamentals for further research and safe control of offshore lifting or lowering.

Effects of dietary supplementation with algal astaxanthin on growth, pigmentation, and antioxidant capacity of the blood parrot ( Cichlasoma citrinellum × Cichlasoma synspilum ) - Feng Li; Shuiying Huang; Xiaoxia Lu; Jun Wang; Mingwei Lin; Yu An; Shaoting Wu; Minggang Cai (Journal of Oceanology and Limnology, 2018)

Berberine protects renal tubular cells against hypoxia/reoxygenation injury via the Sirt1/p53 pathway - Yuanbang Lin; Mingwei Sheng; Yijie Ding; Nan Zhang; Yayue Song; Hongyin Du; Ning Lu; Wenli Yu (Journal of Natural Medicines, 2018)